2008
DOI: 10.1111/j.1399-302x.2008.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mimicry of Aggregatibacter actinomycetemcomitans with β2 glycoprotein I

Abstract: The results suggest that A. actinomycetemcomitans infection may elicit anti-SIRVYK IgG antibodies and modify the anti-TLRVYK antibody response in patients with periodontitis by molecular mimicry with beta2GPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 27 publications
1
31
0
2
Order By: Relevance
“…It has been hypothesized that some anti-CL found in patients without autoimmune disease may result from molecular mimicry of microbial origin (Blank et al 2002). In fact, Wang (Wang et al 2008) demonstrated that patients with A. actinomycetemcomitans infection displayed elevated antibody concentrations to the peptide SIRVYK, a sequence found in A. actinomycetemcomitans that is homologous to TLRVYK. Furthermore, anti-SIRVYK correlated with anti-TLRVYK in patients colonized with A. actinomycetemcomitans.…”
Section: Anti-cardiolipinmentioning
confidence: 99%
“…It has been hypothesized that some anti-CL found in patients without autoimmune disease may result from molecular mimicry of microbial origin (Blank et al 2002). In fact, Wang (Wang et al 2008) demonstrated that patients with A. actinomycetemcomitans infection displayed elevated antibody concentrations to the peptide SIRVYK, a sequence found in A. actinomycetemcomitans that is homologous to TLRVYK. Furthermore, anti-SIRVYK correlated with anti-TLRVYK in patients colonized with A. actinomycetemcomitans.…”
Section: Anti-cardiolipinmentioning
confidence: 99%
“…Because previous studies demonstrated that ␤ 2 GPI shares epitope homology with certain microbial pathogens 37 such as periodontal pathogens, 38 we compared the peptide sequence with known microbial sequences in the Swiss-Prot database using BLASTP. We found that the peptide sequence shared a complete identity (100%) with an epitope of P gingivalis RNA polymerase -70 factor (PDDLPFST; Figure 2A).…”
Section: Identification Of a P Gingivalis Epitope Sharing Complete Idmentioning
confidence: 99%
“…If bacteria have molecular mimicry with a host peptide, immune responses to the bacteria might also attack the host molecule that shares the same sequence, and this autoimmune function might induce systemic diseases [23,24]. Molecular mimicry between periodontopathic bacteria and host molecules, e.g., heat shock proteins [25], β2-glycoprotein I [26], and citrullinated enolase [27], has been reported by several investigators. Antibody response to periodontopathic bacteria is important to protect the periodontal tissue from bacteria.…”
Section: Molecular Mimicrymentioning
confidence: 99%